APLIKASI FORECASTING JUMLAH FREKUENSI PENUMPANG PESAWAT TERBANG LION AIR PADA BANDAR UDARA HALU OLEO DENGAN MENGGUNAKAN METODE LEAST SQUARE - Waode Berlian Ruamiana; Jumadil Nangi; LM Tajidun (semanTIK, 2018)
As the era develops really quickly, the development of technology in transportation also changing rapidly. One of the most transport demands by the public for a long journey today is air transport. Along with the increase of population, the need for air transportation also increased.The airport Halu Oleo is one example of a company that offers its services in the field of aviation. Therefore, the forecast of the number of passengers have become important factors for the company Lion Air, because by knowing the predicted number of passengers in the future of Lion Air can prepare facilities in anticipation of rising passenger numbers.Least Square method (least squares method) or a simple regression analysis is an effective and simple approach to measure the average change in the dependent variable that is related to the increase in the number of units of one or more independent variables. The least squares method is used to determine the linear relationship of the best ways that minimize the number of errors squared data generated by mathematical functions. This method is most often used to predict Y, because the calculation more accurately.Keywords— Lion Air, Least Square method, Forecasting.